Under the shadow of philology; Some notes on translating Hikayat Seri Rama for a modern non-academic audience - Aveling, Harry (Wacana, Journal of the Humanities of Indonesia, 2020)
This article describes some of the issues that arose during the author’s experience of translating the Malay Hikayat Seri Rama into English, as a literary rather than a philological text. These include the choice of a source text, the nature of the language used in the translation, and the treatment of the most distinctive features of the text, including its focus on Rawana, its setting in a Muslim narrative frame, and its use of the worldview of a medieval Malay court. Linguistic issues are discussed through reference to the concept of “units of translation”. This practice can also be utilized in an expanded sense to refer to larger textual units such as sentences, paragraphs, chapters, and parts of the whole text. Finally, a few recurring stylistic issues are noted, such as the use of a repetitive vocabulary, the use of kinship terms for non-kin, and a small number of places where there are no adequate English equivalents for particular words. The article concludes by suggesting that the approaches of the philologist and the literary translator are sometimes antagonistic but can be mutually beneficial.